2011
DOI: 10.2214/ajr.10.5614
|View full text |Cite
|
Sign up to set email alerts
|

C-Arm CT for Assessing Initial Failure of Iodized Oil Accumulation in Chemoembolization of Hepatocellular Carcinoma

Abstract: C-arm CT is nearly equivalent to MDCT for detecting incomplete iodized oil accumulation after TACE, suggesting that the immediate assessment of iodized oil accumulation with C-arm CT without the need to perform follow-up unenhanced MDCT is likely feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The role of CBCT can also be seen in therapy response assessment, in particular for Lipiodol deposition (Fig. 4) [27, 38-41] or for marginal contrast retention with DEB, which is associated with successful treatment outcomes 1 month post-DEB [27]. …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The role of CBCT can also be seen in therapy response assessment, in particular for Lipiodol deposition (Fig. 4) [27, 38-41] or for marginal contrast retention with DEB, which is associated with successful treatment outcomes 1 month post-DEB [27]. …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Incomplete tumor treatment negatively impacts survival (91,92). The imaging characteristics of different chemoembolic agents differ substantially, thus requiring different posttreatment CBCT techniques.…”
Section: Cbct To “Assess” Treatment Success: Rationale and Techniquesmentioning
confidence: 99%
“…Lipiodol is a radiopaque contrast agent, which has also been used as a biomarker for HCC (93). Lipiodol deposition in the tumor is a prognostic factor affecting local recurrence of HCC and may be determined directly during the procedure using unenhanced CBCT, which offers equivalent lipiodol detection accuracy to unenhanced MDCT imaging (91,92,9496). Drug-eluting beads, commonly loaded with doxorubicin (adriamycin), are radiolucent and so are mixed with contrast agent during delivery.…”
Section: Cbct To “Assess” Treatment Success: Rationale and Techniquesmentioning
confidence: 99%
“…For example, Lipiodol®/Lipiodol UltraFluide®, a liquid embolic agent, has been widely used as drugcarrying and blood-vessel-embolic materials in TACE since they could selectively accumulate in intratumoral peripheral vessels [13]. However, many studies indicated Lipiodol had poor properties in drugcontrolled release [14,15], and it was difficult for Lipiodol to achieve long-term embolism due to in vivo rapid elimination [16]. Ivalon® (PVA foam embolization particles), on the other hand, was difficult to flow into peripheral arteries in tumor due to its large size (180-300 μm), but showed excellent long-term embolism in TACE [17].…”
Section: Introductionmentioning
confidence: 99%